Evaluación de bioestimulantes y fertilizantes foliares en el desarrollo del cultivo de maíz (Zea mays L.) en la zona de Ventanas - García Valenzuela, Deivis Manuel (2019)
This experimental work was carried out on the land owned by Mr. Arturo Vicente Litardo Anchundia located in the Pijio Campus at Km 1.5 via Echeandia - Ventanas, belonging to the Ventanas Canton, Los Ríos Province. The area has a humid tropical climate according to Holdribge classification, with an annual temperature of 26.0º C, an annual average rainfall of 2115.9 mm / year, relative humidity of 80% annual average. As a planting material, the Advanta 9139 corn hybrid was used. This experimental work used treatments such as Green Master biostimulants in doses of 1.0 L / ha; Espigold at a dose of 1.0 L / ha; Ecohormones in doses of 0.5 L / ha; Foliar fertilizers Complefol SL in doses of 1.0 L / ha; Ned Combi in doses of 0.5 kg / ha; Active Phyto in doses of 0.5 L / ha and the absolute control without application of products. We used the experimental design of Random Complete Blocks with 7 treatments and 3 repetitions, whose comparison of means was made with the Tukey test. The management of experimental field work was carried out with all agricultural practices and work that the crop requires for its normal development, such as land preparation, planting, weed control, phytosanitary control, fertilization, irrigation and harvesting. Based on the results obtained, it was determined that the biostimulants and foliar fertilizers had a positive influence on the development and yield of the corn crop, in the Ventanas area; the highest plant height, ear insertion height, diameter and length of the cob, grains per ear and weight of 1000 grains was obtained with the application of the foliar fertilizer Complefol SL in doses of 1.0 L / ha at 13, 18 and 30 days after sowing and the highest crop yield with 7344.2 kg / ha and net economic benefit with $ 310.0 was presented when using the foliar fertilizer Complefol SL in doses of 1.0 L / ha